(untitled) (Research, Society and Development, 2021)
Posterior mandible region is considered a highly predicable place for primary stability during dental implant placement. Although, this region can present a significant decrease in bone density, which can lead to implant dislocation during insertion. The present case reports an unusual dislocation of dental implant in a 59 old healthy patient’s mandible and a secure solution for this kind of complication. During the drilling, bone quality type IV was observed. In sequence, implant was abruptly inserted in the perforation site and dropped into the bone marrow. Panoramic radiograph showed the implant inside bone marrow, close to mandibular base. The implant was removed through the surgical site. The screw of the implant prosthesis transfer was used to reach the displaced implant. A second implant with the same dimensions as the first one, differing by the external hexagon, was inserted into the same implant site. Therefore, the authors strongly recommend the use of the presented technique prior to osteotomy on mandibular body, reserving the second in the impossibility of reaching the internal connection of the displaced implant.